2011
DOI: 10.1080/10503307.2010.525759
|View full text |Cite
|
Sign up to set email alerts
|

Change in reflective functioning during psychotherapy—A single-case study

Abstract: It has been suggested that deficits in mentalization are a core problem of borderline personality disorder and that enhancement of mentalization represents a central mechanism of change in psychotherapy with this group of patients. The present single-case study investigates changes in mentalization measured by the Reflective Functioning Scale on the Adult Attachment Interview and its relationship with clinical measures of psychopathology during a long-term psychotherapy. The usefulness of evaluating RF along t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Studies of narrative processes in psychotherapy have used varied research designs ranging from intensive single case designs (Angus & Kagan, 2013;Gullestad & Wilberg, 2011), a single group design with few cases of a specific disorder like depression (Levitt, Korman, & Angus, 2000), two-group designs with either different therapy modalities (Boritz, Angus, Monette, Hollis-Walker, & Warwar, 2011) or a clinical group and matched control group (Ramussen & Angus, 1996). Studies with control groups have primarily used single psychotherapy sessions (Ramussen & Angus, 1996) or a single autobiographical memory test (Reid & Startup, 2010) and this may reflect the resource-intensive nature of qualitative research examining narrative material.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of narrative processes in psychotherapy have used varied research designs ranging from intensive single case designs (Angus & Kagan, 2013;Gullestad & Wilberg, 2011), a single group design with few cases of a specific disorder like depression (Levitt, Korman, & Angus, 2000), two-group designs with either different therapy modalities (Boritz, Angus, Monette, Hollis-Walker, & Warwar, 2011) or a clinical group and matched control group (Ramussen & Angus, 1996). Studies with control groups have primarily used single psychotherapy sessions (Ramussen & Angus, 1996) or a single autobiographical memory test (Reid & Startup, 2010) and this may reflect the resource-intensive nature of qualitative research examining narrative material.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that prompting dysphoric individuals and depressed patients to engage in decentering reduces their categorical recall and increases the focus on their own experiences, including specific memories (Watkins et al, 2000). Besides being relevant for understanding different kinds of psychopathology and effective treatment outcome, the insight into one's own mental processes is also proposed to be important to the processes of psychotherapy itself (Dimaggio et al, 2009Gullestad, Johansen, Høglend, Karterud, & Wilberg, 2013;Gullestad & Wilberg, 2011). In line with this, decentering has been referred to as a key mechanism of mindfulness (Shapiro, Carlson, Astin, & Freedman, 2006) and preliminary evidence indicates that, in addition to facilitating improved health outcomes in patients, mindfulness training for therapists also fosters desirable therapist characteristics, has a beneficial effect on the therapeutic process, and can improve session outcome from the client's perspective (Cigolla & Brown, 2011;Dunn, Callahan, Swift, & Ivanovic, 2013;Ryan, Safran, Doran, & Muran, 2012).…”
mentioning
confidence: 98%
“…Effectiveness and efficacy studies have assessed changes in RF as an outcome variable in personality disorders (Levy et al 2006;Vermote et al 2010;Fischer-Kern et al 2015), panic disorder (Rudden et al 2006), depression (Karlsson and Kermott 2006;Taubner et al 2015), and substance abuse (Grenyer and Middleby-Clements 2003), as well as changes of RF in mothers in parent-child therapy (Müller-Göttken, 2014). Three studies have assessed long-term changes in RF in single-case studies (Szecsödy 2008;Gullestad and Wilberg 2011;Josephs et al 2004). Most studies have employed the gold standard by using the Adult Attachment Interview (AAI) to assess RF (Levy et al 2006;Fischer-Kern et al 2015;Taubner et al 2015) or a shortened version of it (Rudden et al 2006).…”
mentioning
confidence: 99%